A synchronous occurrence of breast cancer and pleural mesothelioma: a case report - Zaheer Ahmad; Hashir Jehanzeb; Saad Noor Hussain; M. Umar; Humna Saleem (Journal of Medical Case Reports)
Abstract Background Malignant mesotheliomas are aggressive forms of tumors arising from mesothelial cells. The most common type is malignant pleural mesothelioma, which progresses rapidly and leads to pleural effusion. It typically affects older men and is strongly associated with asbestos exposure. However, a few studies have reported cases of malignant pleural mesothelioma resulting from non-asbestos factors, including radiotherapy for breast cancer, viruses, chronic inflammation, and BRCA1-associated protein-1-associated genetic mutations. Breast cancer is the most common sporadic cancer among women, and a small percentage of cases are related to genetic factors, such as BRCA1/2 and BRCA1-associated protein-1 mutations. While breast cancer can be linked with other primary malignancies through germline mutations, the synchronous occurrence of breast cancer with pleural mesothelioma is extremely rare. Case presentation We present the case of a 40-year-old Pashtun woman diagnosed with primary breast cancer. She underwent surgery followed by chemotherapy (paclitaxel). During chemotherapy, she developed right-sided chest pain and dyspnea. A computed tomography scan revealed pleural thickening, and a pleural biopsy confirmed the diagnosis of malignant pleural mesothelioma, with positive results for the diagnostic markers WT1 and D240. Conclusion This case represents a rare occurrence of synchronous breast cancer and pleural mesothelioma in a 40-year-old female, and is the first case reported in Khyber Pakhtunkhwa, Pakistan. These findings demonstrate the importance of comprehensive diagnostic testing and the potential role of genetic mutations in concurrent cancers. The challenge of simultaneously treating these cancers highlights the need for further research and the importance of multidisciplinary approaches.